A monoclinic polymorph of sodium birnessite for ultrafast and ultrastable sodium ion storage - Xia, Hui; Zhu, Xiaohui; Liu, Jizi; Liu, Qi; Lan, Si; Zhang, Qinghua; Liu, Xinyu; Seo, Joon Kyo; Chen, Tingting; Gu, Lin; Meng, Ying Shirley (Nature communications, 2018)
Sodium transition metal oxides with layered structures are attractive cathode materials for sodium-ion batteries due to their large theoretical specific capacities. However, these layered oxides suffer from poor cyclability and low rate performance because of structural instability and sluggish electrode kinetics. In the present work, we show the sodiation reaction of Mn 3 O 4 to yield crystal water free NaMnO 2−y−δ (OH) 2y , a monoclinic polymorph of sodium birnessite bearing Na/Mn(OH) 8 hexahedra and Na/MnO 6 octahedra. With the new polymorph, NaMnO 2−y−δ (OH) 2y exhibits an enlarged interlayer distance of about 7 Å, which is in favor of fast sodium ion migration and good structural stability. In combination of the favorable nanosheet morphology, NaMn 2−y−δ (OH) 2y cathode delivers large specific capacity up to 211.9 mAh g –1 , excellent cycle performance (94.6% capacity retention after 1000 cycles), and outstanding rate capability (156.0 mAh g –1 at 50 C). This study demonstrates an effective approach in tailoring the structural and electrochemical properties of birnessite towards superior cathode performance in sodium-ion batteries. Layered Na x MnO 2 cathode suffers from structural instability and sluggish kinetics. Here the authors show a method to yield monoclinic NaMn 2−y−δ (OH) 2y , a new polymorph of Na-birnessite with maximum Na occupancy and enlarged interlayer spacing, enabling outstanding cyclability and rate performance.